Críticas ao sistema jurídico brasileiro de aplicação do princípio da isonomia salarial nos contratos individuais de trabalho: por uma leitura dialética da igualdade - Santos, Rafael Oliveira (2019)
The object of this research is to identify the main legal and labor institutes present in Brazilian legislation, and from this analysis, to identify if the initial hypothesis is confirmed, that all this subsystem is oriented to the practice of a wage isonomy essentially formal, in the philosophical paradigm of Aristotelian logic. Once this hypothesis is confirmed, it is intended to offer some criticism to the way of thinking about this equality, changing this paradigm in favor of a material or dialectical equality, and admitting a substantial inequality as a way of approximation of the similar, by criterion of proportionality, and not only separation from what is not equal